Changing Representation: The Vote of Non-citizen Immigrant Residents in Their New Homeland - Rashkova, Ekaterina R. (Politics of the Low Countries, 2025)
Living in a globalized world, where millions of people no longer live in their countries of birth, we ought to be asking ourselves whether and to what extent the traditional model of representative democracy is changing or needs to change. In particular, to what extent do citizens who live abroad participate in the democratic processes of their home country, and, conversely, what is the relationship with the electoral options in their new homelands? This research note explores the latter aspect by focusing on the Dutch national election held in March 2021. Based on a small sample of survey data, this exploratory analysis shows that non-citizen residents largely support less-established parties that have positioned themselves as parties that want to innovate and bring about new politics. This finding suggests that allowing immigrants to vote at national elections could have a visible impact on election outcomes.